Noncatalyzed Reduction of Nitriles to Primary Amines with Ammonia Borane - Ding, Man; Chang, Jiarui; Mao, Jia-Xue; Zhang, Jie; Chen, Xuenian (Journal of organic chemistry, 2022)
The preparation of primary amines from nitriles has been a subject of continuing interest, and many different methods have been reported for this process. We report in this paper an alternative method for transforming nitriles into primary amines. In this work, a wide range of nitriles were reduced to primary amines by 1.2 equiv of ammonia borane under thermal decomposition conditions without any catalyst and the corresponding primary amines were isolated in good to excellent yields. The reactions are environmentally benign with H2 and NH3 generated as byproducts. The reactions are also tolerant of many functional groups. Nitriles are likely reduced by the in situ-generated aminodiborane, the application of which in organic synthesis has never been reported before. By using our protocol, primary amines containing multifluorinated aromatic rings, which are greatly important in pharmaceutical synthesis and have rarely been prepared via catalytic processes, were successfully prepared.